Enhancing Written Performance in EFL Context: Using Grammar- Focused and Vocabulary- Focused Pre-tasks and Task Repetition - Kavandi, Elham; Ghasemi, Muhammad Hossein (IJRDO- Journal of Educational Research, 2019)
The dominant purpose of this paper is to investigate the impact of grammar-focused and vocabulary-focused pre-tasks and task repetition on Iranian EFL learners’ written performance. Grammar-focused and vocabulary-focused pre-tasks are said to promote learning and prepare students to complete the tasks more effectively. Task repetition is also suggested to help improve learners’ performance in TBLT settings. Forty-five intermediate adult male learners participated in this study. They were randomly divided into two experimental and one control groups. In order to collect the data needed for this piece of research first a demographic questionnaire was used to collect the students’ personal information. Then English writing proficiency test was run to make sure that the participants were homogeneous. And finally, IELTS written tasks were employed to measure the participants’ written performance. Different statistical procedures such as Pearson’s correlation, One-Way ANOVA, post-hoc tests, and paired sample t-tests were employed to analyze the collected data. The results of data analyses indicated that 1) the participants enjoyed the same level of English writing proficiency prior to the implementation of the study, 2) the experimental group learners performed significantly better than the control group learners in terms of foreign language writing, and 3) task repetition had a significant influence on learners’ written performance. It was concluded that both grammar-focused and vocabulary-focused pre-task activities have a significant and positive influence on Iranian EFL learners’ L2 writing performance. Task-repetition was also concluded to have a positive influence on students’ writing performance. The results of this research have clear implications for Iranian foreign language teachers and researchers to employ grammar-focused and vocabulary-focused pre-tasks in their endeavors.